New Model of Arabic Language Evaluation and Test System in the Development of 21st Century Learning Media - Mursyid, Abdul Razak; Hula, Ibnu Rawandhy N. (ELOQUENCE : Journal of Foreign Language, 2024)
Background: This article discusses the Arabic language evaluation and test system using technological media as a goal to help the quality of learning Purpose: This study aims to discuss the Arabic language evaluation and test system in the development of 21st-century learning media in a systematic and organized manner. Method: The method used in this research is library research or literature review is the process of conducting research carried out by a researcher to collect some information and data sets based on various available materials such as reference books, previous research, journal articles, notes, and various kinds of magazines that are closely related to the title of the research to be solved. Results and Discussion: The results of the research and discussion in this study include the development of media based on quizzes, centimeters, and neared applications that can be used in the use of evaluation systems and Arabic language learning tests. Conclusions and Implications: This study concludes that in carrying out an Arabic language evaluation and test system based on the development of Quiziz, centimeter, and Nearpod media, the three applications are very useful in compiling Arabic evaluation and test questions. Because several features are very complete educators can easily assess and measure the extent of students' ability to master learning material.